IL-12 family cytokines and autoimmune diseases: A potential therapeutic target? - Cui, Xiaoyu; Liu, Wu; Jiang, Hanxue; Zhao, Qihan; Hu, Yuehong; Tang, Xinyue; Liu, Xianli; Dai, Haoran; Rui, Hongliang; Liu, Baoli (Journal of translational autoimmunity (Online), 2025)
In recent years, the discovery of IL-12 family cytokines, which includes IL-12, IL-23, IL-27, IL-35, and IL-39, whose biological functions directly or indirectly affect various autoimmune diseases. In autoimmune diseases, IL-12 family cytokines are aberrantly expressed to varying degrees. These cytokines utilize shared subunits to influence T-cell activation and differentiation, thereby regulating the balance of T-cell subsets, which profoundly impacts the onset and progression of autoimmune diseases. In such conditions, IL-12 family members are aberrantly expressed to varying degrees. By exploring their immunomodulatory functions, researchers have identified varying therapeutic potentials for each member. This review examines the physiological functions of the major IL-12 family members and their interactions, discusses their roles in several autoimmune diseases, and summarizes the progress of clinical studies involving monoclonal antibodies targeting IL-12 and IL-23 subunits currently available for treatment.